2022
DOI: 10.3389/fpls.2022.831314
|View full text |Cite
|
Sign up to set email alerts
|

Cold Stress Resistance of Tomato (Solanum lycopersicum) Seedlings Is Enhanced by Light Supplementation From Underneath the Canopy

Abstract: Adverse environmental conditions, such as low temperature (LT), greatly limit the growth and production of tomato. Recently, light-emitting diodes (LEDs) with specific spectra have been increasingly used in horticultural production facilities. The chosen spectrum can affect plant growth, development, and resistance, but the physiological regulatory mechanisms are largely unknown. In this study, we investigated the effects of LED light supplementation (W:B = 2:1, light intensity of 100 μmol⋅m–2⋅s–1, for 4 h/day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 85 publications
(110 reference statements)
0
1
0
Order By: Relevance
“…Previous studies have shown that chilling stress suppresses the photosynthetic capacity of plants (Lu et al 2022;Zhang et al 2022). Reduced stomatal conductance due to chilling stress results in the inhibition of carbon fixation, which limits CO 2 availability at carboxylation sites in the chloroplast, resulting in photoinhibition and generation of high levels of ROS (Mahajan & Tuteja 2005;Clemente-Moreno et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that chilling stress suppresses the photosynthetic capacity of plants (Lu et al 2022;Zhang et al 2022). Reduced stomatal conductance due to chilling stress results in the inhibition of carbon fixation, which limits CO 2 availability at carboxylation sites in the chloroplast, resulting in photoinhibition and generation of high levels of ROS (Mahajan & Tuteja 2005;Clemente-Moreno et al 2020).…”
Section: Discussionmentioning
confidence: 99%